STRATEGIES FOR ORGANIZATIONAL CHANGE IN SMEs - Milder Gómez Fernández, Hugo; Álvarez, Karina; Ramona Jiménez Ayala, Liliana (Revista Gênero e Interdisciplinaridade, 2023)
In this final degree project called “Strategy for organizational change in SMEs” whose objective is to identify the changes that must be promoted for organizational restructuring, to face the challenges that require a lot of preparation on the part of professionals. administrative managers of the company and thus direct the officials towards success. According to the research carried out, there is a diversity of strategies that can be implemented taking into account what level the entity is at, change in the organization is very necessary because, in the world of commerce, there is very rapid progress and a current system which is, the technology that surprises more every day. On the other hand, the quantitative approach is adopted as a study method, using a questionnaire with 10 questions addressed to senior officials of 3 companies in Ciudad del Este from different sectors. The responses were used to analyze the different types of problems that the companies had and mainly to know the strategies they have used to solve or reduce the effects of these problems. With the research done and the results obtained, it is concluded that companies need an organizational change by planning techniques for a good work environment.